Cytotoxicity and Immune Dysfunction of Dendritic Cells Caused by Graphene Oxide - Yang, Zhiwen; Pan, Yongning; Chen, Tingting; Li, Li; Zou, Wenyi; Liu, Dongmeng; Xue, Dahui; Wang, Xiaomei; Lin, Guimiao (Frontiers in Pharmacology, 2020)
Graphene, known as “black gold”, has important applications in various fields. In previous studies, it has been proved that graphene oxide (GO) which is a derivative of graphene has low toxicity. However, the immunotoxicity of GO has not been fully elucidated. In this work, we used DC2.4 cell line to investigate the in vitro immunotoxicity of two types of GO, mono-layer GO (mono-GO) and multi-layer GO (multi- GO). We found that mono-GO had less effect on cell viability than multi-GO, but both mono-GO and multi-GO significantly induced the generation of ROS in DC2.4 cells. Interestingly, mono-GO caused DC2.4 cells to aggregate, thus changed the cell morphology significantly. However, no similar influence occurred for multi-GO. In addition, the results showed that these two GOs obviously enhance the release of TNF-α by DC2.4 cells with and without LPS stimulation. GO did not affect the level of IL-6 released from DC2.4 cells, but multi-GO promoted the release of IL-6 while mono-GO inhibited the production of IL-6 when cells were in response to LPS stimulation. Whole-transcriptome sequencing analysis found some immune-related differentially expressed genes including H2-DMb1, Ncbp3, Oas2, Men1, Fas, Cd320, Cd244 and Tinagl1 which are engaged in the immune system process. These results suggested that both mono-GO and multi-GO are immunotoxic to DC2.4 cells, which provides important basis for subsequent biological and clinical medical applications.